Education and Training on the Use of Personal Protective Equipment (PPE) as a Strategy to Improve Patient Safety in Preventing Nosocomial Infections - Alfi Syahar Yakub; Sukriyadi Adi (Celebes Health Journal, 2026)
Nosocomial infections remain a significant problem in the healthcare system due to increased morbidity, mortality, and healthcare costs. The use of personal protective equipment (PPE) is a key strategy in infection prevention and patient safety improvement. This study aims to analyze the role of education and training in PPE use as a strategy to improve patient safety in preventing nosocomial infections among healthcare workers. This study used an observational analytical design with a cross-sectional approach conducted at Madising Pinrang Hospital from December 2025–January 2026. The study sample consisted of 35 healthcare workers selected using a total sampling technique. Data were collected using a questionnaire and analyzed through descriptive, bivariate, and logistic regression analyses. The results showed that knowledge, training in PPE use, and availability of PPE were significantly associated with PPE use, while attitudes did not show a significant relationship. PPE availability was the dominant factor influencing PPE use. Education, training, and facility support are important strategies to improve compliance with PPE use in preventing nosocomial infections.